Rural women empowerment through self help groups in Nigeria: the role of participation and volunteerism - Abu Samah, Asnarulkhadi; Ahmad, Nobaya; Ndaeji, Muhammad Ndas (Marsland Press, 2013)
Active participation and volunteerism of rural women in self help group’s activities are vital for sustainable women development. This paper seeks to examine the role of participation and volunteerism in SHG’s activities towards women’s empowerment. Participation and volunteerism in SHGs by women occur as a result of their awareness of their felt needs and that they can always come together to solve their problems through collective efforts. The general aim of this paper is to describe how participation and volunteerism in women’s SHGs reinforce a sense of personal ability that creates expectation for a successful women development. The paper also briefly looks at the extent to which rural women are empowered through and genuine participation of the members. A sample of 282 SHG members were selected through simple random (lottery method) out of 30 SHGs identified in agricultural activities from the three senatorial districts of Niger State and a schedule was designed and administered among the respondents. The results of this study indicated that majority of the respondents had participated in SHGs voluntary (Self Mobilization) and were fully motivated and involved in carrying out every aspect of group activities. The study also revealed that respondents had shown greater level of volunteerism towards the success of the group approaches. It was observed that the majority of the respondents had always encouraged themselves for maximum participation towards the success of the group goals. Thus, with self mobilization type of participation and a high spirit of volunteerism within individuals and groups in organization, the success of building a group, community and society will be fully attainable.